Analisis Pengaruh Perendaman Benda Uji Terhadap Mutu Beton Menggunakan Metode Statistical Quality Control di PT CAW - Anak Agung Gede Weda Baweswara; I Gusti Ngurah Priambadi; Alam Satria (JURNAL RISET DAN APLIKASI TEKNIK INDUSTRI, 2025)
Among the various factors that can impact the strength of concrete, the curing method is a key factor. This treatment aims to maintain moisture on the concrete surface, allowing the hydration process to run optimally. Generally, hydration lasts for 28 days, allowing the concrete to reach a strength that meets the established quality standards. However, various conditions in the field are one of the factors that prevent curing from being carried out perfectly. In this study, the researcher wanted to show how the curing process affects the strength of the resulting concrete. The test used concrete samples with curing ages of 7, 14, and 28 days, along with cylindrical test objects. The test results showed that the compressive strength of the concrete increased with increasing curing age, namely 24.11 MPa (7 days), 28.42 MPa (14 days), and 32.56 MPa (28 days), meeting the design quality of 30 MPa. SQC analysis was carried out using the I diagram and MR diagram for each age group of test objects. The results showed that the entire testing process fell within the quality control limits, indicating that the curing process was considered stable. This study confirms the importance of optimal concrete curing for up to 28 days to achieve maximum compressive strength